G304(P) Rcpch best practice guideline to newborn examination to reduce the prevalence of delayed detection of cleft palate (cp). (27th April 2015) - Habel, A; Dudley, J; Allister, J; Elliman, D; Jokinen, M; Marlow, N; Marsh, C; McElroy, H; Preston, R; Slator, R; Soe, A; Tuckey, M; et al.
Abstract : Introduction: The UK prevalence of Cleft Palate (CP) without cleft lip is 1 in 1, 750 live births. Half of CP have associated malformations and syndromes. The prevalence of delayed detection in the first 24 h after birth is 30%, 16% more than 72 h, 7% under three months of age, 3% under year and 2% over one year old. Potentially unnecessary delay in appropriate management, parental distress, and litigation occur. Strong circumstantial evidence suggests the method of palate examination as the cause. Aim: Develop recommendations for optimal examination of the palate during routine newborn examination to ensure early detection of CP. Methods: A consensus guidelines group was led by the RCPCH, including parent groups and key professional stakeholders. The RCPCH standards for development of clinical guidelines in paediatrics and child health were followed. A systematic review with methodological advice from the RCPCH clinical standards team was undertaken. Where there was limited evidence to support recommendations for practice a Delphi consensus method was carried out. When Delphi consensus was not reached, recommendations were based on working group consensus. Results: Examination of the newborn baby's hard and soft palate should be carried out by visual inspection and recorded in the Child Health Record. Use a torch and method of depressing the tongue to visualise the whole palate. Parents should be informed if the whole palate (including the full length of the soft palate) has not been visualised. Failure to visually inspect the whole palate at first attempt should be followed by repeat visual examination within 24 h. Conclusion: Trusts should provide training on the correct method of visual inspection of the palate to all healthcare professionals required to carry out newborn examinations. http://www.rcpch.ac.uk/improving-child-health/clinical-guidelines-and-standards/published-rcpch/inspection-neonatal-palate